Innate and Adaptive Immune Responses Against Microsporidia Infection in Mammals - Han, Yinze; Gao, Hailong; Xu, Jinzhi; Luo, Jian; Han, Bing; Bao, Jialing; Pan, Guoqing; Li, Tian; Zhou, Zeyang (Frontiers in Microbiology, 2020)
Microsporidia are obligate intracellular and eukaryotic pathogens that can infect immunocompromised and immunocompetent mammals, including humans. Both innate and adaptive immune systems play important roles against microsporidian infection. The innate immune system can partially eliminate the infection by immune cells, such as gamma delta T cell, natural killer cells, macrophages and dendritic cells, and present the pathogens to lymphocytes. The innate immune cells can also prime and enhance the adaptive immune response via surface molecules and secreted cytokines. The adaptive immune system is critical to eliminate microsporidian infection by activating cytotoxic T lymphocyte and humoral immune responses, and feedback regulation of the innate immune mechanism. In this review, we will discuss the cellular and molecular responses and functions of innate and adaptive immune systems against microsporidian infection.